Phyllanthus emblica: Phytochemistry, Antimicrobial Potential with Antibiotic Enhancement, and Toxicity Insights - Gagan Tiwana; Ian Edwin Cock; Matthew James Cheesman (Microorganisms)
Phyllanthus emblica Linn. (commonly known as Amla or Indian Gooseberry) is commonly used in Ayurvedic medicine to treat respiratory infections, skin disorders, and gastrointestinal issues. The fruit contains an abundance of polyphenols, which contribute to its strong antioxidant properties. The antibacterial activity of fruit extracts derived from P. emblica against Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae was determined along with the antibiotic-resistant variants extended-spectrum β-lactamase (ESBL) E. coli, methicillin-resistant S. aureus (MRSA), and ESBL K. pneumoniae. Disc diffusion and broth dilution assays were conducted to assess the activity of aqueous, methanolic, and ethyl acetate extracts, with large zones of inhibition of up to 15 mm on agar observed for S. aureus and MRSA. Minimum inhibitory concentration (MIC) values ranging from 158 to 1725 µg/mL were calculated. The aqueous and methanolic extracts of P. emblica were less active against E. coli, ESBL E. coli, K. pneumoniae, and ESBL K. pneumoniae, with the only noteworthy MIC (633 µg/mL) observed for the aqueous extract against K. pneumoniae. Interestingly, a lack of inhibition was observed on agar for any of the extracts against these bacteria. Liquid chromatography–mass spectrometry (LC-MS) analysis identified several notable flavonoids, phenolic acids, terpenoids, and tannins. Notably, Artemia nauplii bioassays indicated that all extracts were nontoxic. The antibacterial activity and absence of toxicity in P. emblica extracts suggest their potential as candidates for antibiotic development, highlighting the need for further mechanistic and phytochemical investigations.